Analisis tingkat pengetahuan penggunaan antibiotik di masyarakat Desa Lebah Sempage Kabupaten Lombok Barat - Candra Eka Puspitasari; Handa Muliasari; Agus Dwi Ananto (Universitas Mataram, 2022)
Antibiotics are drugs used to treat infections caused by bacteria. The results of RISKESDAS in 2013 showed that there were 27.8% of the public storing antibiotics without a doctor's prescription, which could lead to bacterial resistance. One of the factors that influence the use of antibiotics in community is the level of knowledge. The purpose of this study was to determine the level of public knowledge regarding the use of antibiotics using the CBIA (Active Human Learning Way) method. This research is descriptive using the CBIA method. Respondents were given a pre-test questionnaire followed by the delivery of material related to antibiotics, then continued with the post-test. The results showed that there was an increase in public knowledge regarding the use of antibiotics by 16.25% using the CBIA method.